2018
DOI: 10.1096/fj.201800299r
|View full text |Cite
|
Sign up to set email alerts
|

Negative feedback loop of autophagy and endoplasmic reticulum stress in rapamycin protection against renal ischemia‐reperfusion injury during initial reperfusion phase

Abstract: Rapamycin, an immunosuppressant, is widely used in patients with kidney transplant. However, the therapeutic effects of rapamycin remain controversial. Additionally, previous studies have revealed deleterious effects of rapamycin predominantly when administered for ≥24 h. Few studies, however, have focused on the short-term effects of rapamycin administered only during the initial reperfusion phase. As such, we designed this study to explore the potential effects and mechanisms of rapamycin under a specific th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…They proposed a negative-feedback loop between autophagy and ER stress during the initial reperfusion phase of renal ischemiareperfusion injury (X. Li et al, 2018). Then what on earth the molecular mechanism of the interplay between ER stress and autophagy in VEGF-A-induced angiogenesis?…”
Section: N-acetyl-l-cysteine Decreased Ros Production and Mitigated Vegf-a-induced Er Stress And Autophagy Activation In Huvecsmentioning
confidence: 99%
“…They proposed a negative-feedback loop between autophagy and ER stress during the initial reperfusion phase of renal ischemiareperfusion injury (X. Li et al, 2018). Then what on earth the molecular mechanism of the interplay between ER stress and autophagy in VEGF-A-induced angiogenesis?…”
Section: N-acetyl-l-cysteine Decreased Ros Production and Mitigated Vegf-a-induced Er Stress And Autophagy Activation In Huvecsmentioning
confidence: 99%
“…Rapamycin, an immunosuppressive agent and mTOR inhibitor, exerts cytoprotective effects in both cell and animal models of ischemia [18,19]. The available data suggest that rapamycin activates protective autophagy and inhibits ER stress in ischemic neurons, hepatocytes and nephrons [20][21][22]. However, whether up-regulation of autophagy and attenuation of ER stress by rapamycin has a protective effect on ischemic ECs remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several reports indicate that renal ER stress is involved in the process of I/R-evoked AKI [810]. ER stress is mediated by three transmembrane ER-resident stress sensors including inositol-requiring enzyme 1 (IRE1), PKR-like ER kinase (PERK), and activating transcription factor (ATF6) [31].…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent report, oxidative stress played important roles during I/R-evoked AKI [7]. On the other hand, several studies found that renal endoplasmic reticulum (ER) stress was involved in the pathogenesis of I/R-evoked AKI [810].…”
Section: Introductionmentioning
confidence: 99%